Digital Marketing Strategy for Woven Tie Fabrics in Kumpang Ilong Village, Sekadau District - Elvi, Fitria; Stefanus Masiun; Adil Bertus AS (LPPM Universitas Muhammadiyah Tasikmalaya, 2025)
Local products represent the artistic craftsmanship of the local community and serve as part of the preservation of local culture. Additionally, they are a vital source of livelihood for local residents, supporting their household economy. The woven ikat fabric of Kumpang Ilong Village is an authentic creation of the village’s original residents, passed down from generation to generation. Preserving this traditional craft is crucial as a means of maintaining the community’s cultural identity. The purpose of this community service initiative is to assist the Kumpang Ilong Village ikat weaving group in marketing their products, particularly through digital platforms such as Facebook and Instagram. By leveraging social media, the aim is to expand the market reach beyond the local community to a wider audience outside Sekadau District, ultimately increasing sales and supporting the household economy while preserving this traditional artwork. The method used in this community service activity involves a combination of theoretical lectures and hands-on training. Participants are first introduced to the basic concepts of digital marketing, followed by direct training sessions where they create Facebook and Instagram accounts. One designated group representative is then tasked with uploading content related to their activities and weaving products on these social media platforms. As a result of this community service program, members of the Kumpang Ilong Village weaving group now have a platform to promote and sell their products. Moreover, participants have gained a better understanding of how to utilize social media, such as Facebook and Instagram, as effective marketing tools without difficulties.